Um serviço de certificação digital para plataformas de middleware - Batista, Caio Sergio de Vasconcelos (2006)
Nowadays due to the security vulnerability of distributed systems, it is needed mechanisms to guarantee the security requirements of distributed objects communications. Middleware Platforms component integration platforms provide security functions that typically offer services for auditing, for guarantee messages protection, authentication, and access control. In order to support these functions, middleware platforms use digital certificates that are provided and managed by external entities. However, most middleware platforms do not define requirements to get, to maintain, to validate and to delegate digital certificates. In addition, most digital certification systems use X.509 certificates that are complex and have a lot of attributes. In order to address these problems, this work proposes a digital certification generic service for middleware platforms. This service provides flexibility via the joint use of public key certificates, to implement the authentication function, and attributes certificates to the authorization function. It also supports delegation. Certificate based access control is transparent for objects. The proposed service defines the digital certificate format, the store and retrieval system, certificate validation and support for delegation. In order to validate the proposed architecture, this work presents the implementation of the digital certification service for the CORBA middleware platform and a case study that illustrates the service functionalities